FACTOR INFLUENCING THE LOYALTY OF DOMESTIC AND FOREIGN TOURISTS - Munandar, Jono M. (Universitas Brawijaya, Indonesia, 2021)
The Tourist Information Center (TIC) Soekarno Hatta International Airport Jakarta is an institution with service activities with a core of tourism marketing and promotion through the delivery of tourist information to domestic and foreign tourists visiting the TIC booth. That research was conducted to determine the effect of the quality of the physical environment, the quality of interaction of front liner officers, the quality of service results, and the quality of e technology provided by TIC on the loyalty of domestic and foreign tourists as the dependent variable. This study uses quantitative methods using a questionnaire in data collection. Sampling using accidental sampling with research variables as many as 35. At the same time, the number of respondents involved consisted of 69 domestic tourists and 106 foreign tourists. Furthermore, the data analysis used Structural Equation Modeling (SEM) Smart PLS 2.0 program. The results of testing the first hypothesis on domestic tourists show the positive influence of interaction on tourist loyalty. The path coefficient value is greater than the t table and p-value. Testing the second hypothesis on foreign tourists shows the positive influence between the quality of the physical environment and the quality of interaction on tourist loyalty. The coefficient value of the environmental quality pathway is greater than the t table and the p-value.